Directory of associations in Barbados - Devonish, Hazelyn E., comp. (Public Library. Reference Department BridgetownBB, 1983)
Lists national associations concerned with health, education, industry and commerce, industrial relations, science and technology, agriculture, horticulture, community development, women, social welfare, youth, environment, creative arts and culture, religion, sports, and miscellaneous subjects. Lists regional and international organizations with offices or headquarters located in Barbados. Each associations' profile contains information including its objectives, membership, special services, publications and sources of financing.